Comparative Anatomy of Labyrinth and Gill of Catfish (Clarias gariepinus) (Burchell, 1822) and Snakehead Fish (Channa striata) (Bloch, 1793) - Ina Karlina; Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
Dumbo catfish (Clarias gariepinus) and Gabus (Channa striata) have additional organ respiratory system structures in the gills, called labyrinth. This organ is a tool for fish to take oxygen directly from the air so that it can live in low oxygen habitats. Both fish have differences at the Order level. Catfish is an order of Siluriformes as Gabus is an order of Perciformes. The purpose of this study was to distinguish the anatomy and histology of the gill structure and labyrinth in both fish. The macroanatomy observation was conveyed by dissection to determine the gill topography in the two fish species. Histology preparations were carried out using the paraffin method and using Hematoxylin-Eosin (HE) staining that showed in the labyrinth organ there were many blood vessels to bind oxygen then distributed to all parts of the fish's body.